Park7 deletion leads to sex-specific transcriptome changes involving NRF2-CYP1B1 axis in mouse midbrain astrocytes - Sergio Helgueta; Tony Heurtaux; Alessia Sciortino; Yujuan Gui; Jochen Ohnmacht; Pauline Mencke; Ibrahim Boussaad; Rashi Halder; Pierre Garcia; Rejko Krüger; Michel Mittelbronn; Manuel Buttini; et al. (npj Parkinson's Disease)
Abstract Loss-of-function mutations in PARK7, encoding for DJ-1, can lead to early onset Parkinson’s disease (PD). In mice, Park7 deletion leads to dopaminergic deficits during aging, and increased sensitivity to oxidative stress. However, the severity of the reported phenotypes varies. To understand the early molecular changes upon loss of DJ-1, we performed transcriptomic profiling of midbrain sections from young mice. While at 3 months the transcriptomes of both male and female mice were unchanged compared to their wildtype littermates, an extensive deregulation was observed in 8 month-old males. The affected genes are involved in processes like focal adhesion, extracellular matrix interaction, and epithelial-to-mesenchymal transition (EMT), and enriched for primary target genes of NRF2. Consistently, the antioxidant response was altered specifically in the midbrain of male DJ-1 deficient mice. Many of the misregulated genes are known target genes of estrogen and retinoic acid signaling and show sex-specific expression in wildtype mice. Depletion of DJ-1 or NRF2 in male primary astrocytes recapitulated many of the in vivo changes, including downregulation of CYP1B1, an enzyme involved in estrogen and retinoic acid metabolism. Interestingly, knock-down of CYP1B1 led to gene expression changes in focal adhesion and EMT in primary male astrocytes. Finally, male iPSC-derived astrocytes with loss of function mutation in the PARK7 gene also showed changes in the EMT pathway and NRF2 target genes. Taken together, our data indicate that loss of Park7 leads to sex-specific gene expression changes through astrocytic alterations in the NRF2-CYP1B1 axis, suggesting higher sensitivity of males to loss of DJ-1.